Optimalisasi Brand Awareness Pada PT X Melalui Event Marketing - Dinah, Syafi'ah; Sutisna, Ma'mun (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
The increasingly intense business competition, particularly among Micro, Small, and Medium Enterprises (MSMEs), poses significant challenges for business actors to maintain their existence amidst the growing number of competitors. This study aims to analyze the impact of event marketing on brand awareness for food and beverage companies in Bandung. The data collection method employed in this study is qualitative, using time-series analysis. The results show that event marketing positively influences the brand awareness of Company X, as evidenced by an increase in searches on Google Trends.